Multistage Conversion of Eucheuma cottonii Residues into Third Generation L-Lactic Acid - Chong, Soo Ling (Curtin University, 2024)
The COVID-19 pandemic increased single-use plastic demand, highlighting the need for sustainable alternatives like polylactic acid (PLA) from biodegradable sources. This study explores using Eucheuma cottonii residues for L-Lactic acid (L-LA) production, achieving significant yields through ultrasonic-assisted molten salts hydrates pretreatment. Optimal conditions for L-LA extraction were identified, and exergy analysis across biorefinery scenarios showed the integrated plant had high efficiency and sustainability, demonstrating the potential of macroalgae-based biorefineries for eco-friendly bioplastic production.